Introduction to Swiss Law - Thier, Andreas (sui generis Verlag, 2022)
What are the origins of direct democracy in Switzerland? How does the Swiss judiciary function? What are the principles of Swiss civil, contract and administrative law? What is the role of public service broadcasting in the political decision-making process? What are the leading cases in tax law? What forms of euthanasia are legal in Switzerland? In this introduction 19 legal scholars of the University of Zurich Law Faculty try to answer these questions and give the reader an overview of Swiss public, private, and criminal law. As the first comprehensive introduction to Swiss law in English, it is addressed to both lawyers from abroad and incoming students to the University of Zurich.